A System Design to Create Mixed 360 Video and 3D Content for Virtual Field Trip - Li, Liangding; Carnell, Stephanie; Reiners, Dirk; Cruz-Neira, Carolina (IEEE International Symposium on Mixed and Augmented Reality Workshops (Online), 2022)
As VR becomes more widely accessible, an increasing number of VR educational solutions have been proposed for remote teaching. However, most of the current virtual reality teaching platforms are not friendly for non-VR educators to create immersive custom scenes. Virtual reality content development still needs expertise and is time-consuming, even with the growing wave of 3D digitization efforts. We present a prototype system to address the challenge of using VR as a tool to enable educators to create immersive collaborative field experiences in a manner that they can build their own instructional content as a combination of real-time 3D assets, immersive video, and interaction. This system combines the advantage of 360 videos and 3D models. 360 video serves as a backdrop to capture environmental detail and dynamic changes. 3D models could be added at runtime via our web-based application for detailed observation and interaction. We present the system performance analysis, lessons learned from system development, and suggestions for further research. We live-streamed a field trip event from the seashore to a local science center with the help of marine biologists and conducted a system performance analysis. We also present system limitations at the current stage and suggestions for future research.